GE_GERICHTE P/18210/2024 vom 21. Januar 2025 - GE Cour de justice (2025)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;INFRACTIONS CONTRE LE PATRIMOINE;AVOCAT;MANDANT | CPP.310.al1; CP.31; CP.138; CP.158; CP.146; CP.151; CP.322novies